Analysis Of The Influence Of Monetary Policy On Economic Growth: Case Study In Developing Countries - Iwan Lubis (Sean Institute, 2023)
This research discusses the relationship between monetary policy and economic growth in developing countries with a focus on effective monetary policy strategies. The main aim of this research is to increase economic growth to improve community welfare and overcome social issues such as unemployment and poverty. The study also highlights the importance of global competitiveness, macroeconomic stability, investment in infrastructure development, education, and health services. In this context, monetary policies that support economic growth are identified as key to achieving this goal. This research uses regression analysis with economic data from developing countries to measure the relationship between monetary policy variables and economic growth. The research results show that reducing interest rates and adequate credit availability can stimulate investment, consumption and growth in the MSME sector. However, the research also highlights the complexity of translating these findings into real policy, requiring coordination between monetary, fiscal policies and a deep understanding of local social and political dynamics.